Fields on Fire: Impact and Alternatives to Stubble Burning in India - Kumari, Rimsha; Sharma, Dushyant; Jaswal, Shivam Kumar; Kaushal, Shilpa (International Journal of Economic Plants, 2023)
In almost all states of India, crop residue burning is a common practice that has induced detrimental effects on the environment, soil, and health. Although stubble burning is a felony under Section 188 of the Indian Penal Code (IPC) and the Air and Pollution Control Act (may be utilised for cow feed, composted with manure, rural roofing, beverage production, packaging materials, and bioethanol, among others) but these are adopted rarely because of unawareness. According to various surveys, farmers practice crop residue burning in many states in India. This is mainly due to the government’s silence, which cannot stop such activities. The purpose of this review is to illustrate the current state of stubble-burning procedures for agricultural waste disposal in India and present numerous potential strategies for crop residue valorisation Overall, this review paper gives an in-depth overview of the detrimental impacts of agricultural waste burning in India, as well as other, more promising management options, such as the use of bioenergy. If widely implemented, these strategies could not only reduce the negative environmental effects of crop residue management, but also add value to the crop global agricultural industry.